Using Taguchi Function to Reduce External Failure Costs / A Case Study in General Company for Textiles and Leather Industries/ Cotton Factory (Medical Products Factory) - Sameer Kamil Al-Kateeb; Mahmood Tareq Mahmood (Journal of Madenat Alelem University College, 2021)
Objectives: The purpose of the reseach is to apply the Taguchi quality loss function in Iraqi medical products factory to show the external failure costs and losses occure at the factory by identifying and addressing varincess in the production processes and helping the factory to produce products within the targeted value and quality to achieve a reduction in the cost of external failure.                                                                                                  Methodology: The research started from the problem of high external failure costs in the factory of medical products, low quality of medical products and inability of the factory to compete in the market, and directing customers to alternative products and competitive quality and higher price is lower.                                                                                                        Approach: The researcher adopted case study methodology as the appropriate method to reach the objectives of the research. A sample of the factory products was selected (The product of medical backpack) to represent the sample of the study, the statistical methods of their work (Taguchi function, quality control panels).                                                 Style of analysis: The arithmetic mean and range maps were used in preparation for the application of the Taguchi function, to determine the value of losses for the medical backpack product (study sample).                                                              Results: The research concluded a number of conclusions, the most important of which is that there are costs of external failure and losses borne by the medical products factory due to the disparity or away from the target quality, as the medical backpack product recorded significant losses annually in the factory and the reason is the deviation of the performance of the medical backpack product index (research sample) About value and quality targeted.